2014
DOI: 10.1371/journal.pone.0097444
|View full text |Cite
|
Sign up to set email alerts
|

Lesions in the Posterior Visual Pathway Promote Trans-Synaptic Degeneration of Retinal Ganglion Cells

Abstract: ObjectiveRetrograde trans-synaptic degeneration of retinal ganglion cell layer (GCL) has been proposed as one of the mechanisms contributing to permanent disability after visual pathway damage. We set out to test this mechanism taking advantage of the new methods for imaging the macula with high resolution by optical coherence tomography (OCT) in patients with lesions in the posterior visual pathway. Additionally, we explored the association between thinning of GCL as an imaging marker of visual impairment suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 17 publications
(18 reference statements)
0
60
0
Order By: Relevance
“…The correlation between the GCIP thinning and the VF defect may indeed be even stronger, as the GCIP thickness in eyes in which the VF was unobtainable due to poor visual function is significantly lower than the mean for the group. While point-to-point topographical correlation between the macular structures and the VF is not entirely established, the area represented by the scan is thought to represent 15°to 20°of the visual field [19]. Interestingly, the fact that we did not find a correlation between VF impairment and the GCIP thickness at baseline suggests that while significant damage occurs early in the course of AION, some structural changes are not fully established until after 1 month.…”
Section: Discussionmentioning
confidence: 72%
“…The correlation between the GCIP thinning and the VF defect may indeed be even stronger, as the GCIP thickness in eyes in which the VF was unobtainable due to poor visual function is significantly lower than the mean for the group. While point-to-point topographical correlation between the macular structures and the VF is not entirely established, the area represented by the scan is thought to represent 15°to 20°of the visual field [19]. Interestingly, the fact that we did not find a correlation between VF impairment and the GCIP thickness at baseline suggests that while significant damage occurs early in the course of AION, some structural changes are not fully established until after 1 month.…”
Section: Discussionmentioning
confidence: 72%
“…Evidence from OCT studies also supports a role for TRD in disorders of the posterior visual pathway [34,35,67,68] with visual field defects in these disorders correlating best with macular GCL thickness than with RNFL thickness [67,68]. Likewise, OCT findings in AD suggest the contribution of TRD in the pathophysiology of visual changes.…”
Section: Pathological Changes In the Retina And Optic Nervementioning
confidence: 86%
“…In a subsequent study by this group, 5 there was a detectable thinning of RNFL after 100 days of the insult, with greater loss occurring in the first 1-2 years. Only case reports 3,24 and small-sample studies [25][26][27] have reported a thinning of the RGC layer in the hemiretina of patients with either mixed posterior lesions or isolated PCA ischaemic events. To our knowledge, this is the first case-control study with patients with unilateral PCA ischaemic lesions.…”
Section: Discussionmentioning
confidence: 99%